Treatment of refractory obsessive–compulsive disorder with nutraceuticals (TRON): a 20-week, open label pilot study. (21st October 2022) - Sarris, Jerome; Byrne, Gerard J.; Oliver, Georgina; Cribb, Lachlan; Blair-West, Scott; Castle, David; Dean, Olivia M.; Camfield, David A.; Brakoulias, Vlasios; Bousman, Chad; Dowling, Nathan; Ee, Carolyn; et al.
Abstract: Background: Obsessive–compulsive disorder (OCD) is often challenging to treat and resistant to psychological interventions and prescribed medications. The adjunctive use of nutraceuticals with potential neuromodulatory effects on underpinning pathways such as the glutamatergic and serotonergic systems is one novel approach. Objective: To assess the effectiveness and safety of a purpose-formulated combination of nutraceuticals in treating OCD: N -acetyl cysteine, L-theanine, zinc, magnesium, pyridoxal-5′ phosphate, and selenium. Methods: A 20-week open label proof-of-concept study was undertaken involving 28 participants with treatment-resistant DSM-5-diagnosed OCD, during 2017 to 2020. The primary outcome measure was the Yale-Brown Obsessive–Compulsive Scale (YBOCS), administered every 4 weeks. Results: An intention-to-treat analysis revealed an estimated mean reduction across time (baseline to week-20) on the YBOCS total score of −7.13 (95% confidence interval = −9.24, −5.01), with a mean reduction of −1.21 points per post-baseline visit ( P  ≤ .001). At 20-weeks, 23% of the participants were considered "responders" (YBOCS ≥35% reduction and "very much" or "much improved" on the Clinical Global Impression-Improvement scale). Statistically significant improvements were also revealed on all secondary outcomes (eg, mood, anxiety, and quality of life). Notably, treatment response on OCD outcome scales (eg, YBOCS) was greatest in those with lower baseline symptom levels, while response was limited in those with relatively more severe OCD. Conclusions: While this pilot study lacks placebo-control, the significant time effect in this treatment-resistant OCD population is encouraging and suggests potential utility especially for those with lower symptom levels. Our findings need to be confirmed or refuted via a follow-up placebo-controlled study.